THE REPRESENTATION OF SINGLE MOTHER'S DUAL ROLE IN "IBU ORA SARE" SHORT FILM (CHARLES S. PEIRCE SEMIOTIC ANALYSIS) - Nahumury, Amanda Putri; Tania, Adelia Septiani Restanti; Nugraha, Nugraha; Antony, Rian (Jurnal Komunikasi dan Media, 2024)
A common social trend is the rise in single-parent families, where children are primarily raised by one parent—either the father or the mother. In Indonesia, single mothers, more prevalent than single fathers, often face bad stigma from society. The research then delves into the dual role of single mothers depicted in the film Ibu Ora Sare using Charles S. Peirce's semiotic analysis. The research findings reveal that single mothers defy the negative stereotypes imposed by society. In the film, Ibu Ora Sare, Gogon’s mother also juggles earning a livelihood, taking Gogon to school, and doing tasks which typically associated with fathers. Single mothers juggling multiple roles should not face unwarranted criticism as they adeptly fulfill their responsibilities—also, the role of the father is already replaced. The research findings provide insights into single mothers' dual responsibilities. Future studies are encouraged to explore deeper feminism's theoretical foundations in this context.